CONTROL OF A REACTION-DIFFUSION SYSTEM: APPLICATION ON A SEIR EPIDEMIC MODE. (2021) - ALABKARI, AMINE; KOURRAD, AHMED; ADNAOUI, KHALID; LAAROUSSI, ADIL EL ALAMI; SOUKHER, NAIMA; BENNAR, ABDELKARIM
No abstract available